Electric Power Loss Reduction Technique for Power Distribution System - Jumeren, Mohammad Hafeiz (Universiti Teknologi Petronas, 2004)
Distribution system forms an important part of the electrical power system connecting high voltage transmission lines to low voltage consumers through feeders, distributors and service mains. Losses in the distribution system vary up to 70% of the total losses. Investigating techniques for the reduction of these losses will be the aim of this project. The project title is 'Electric Power Loss Reduction Techniques for Power Distribution System'. Continuous and on-going research work is being conducted, with an infinite number of literatures done on thepower distribution system. Various factors have beenidentified to be the causes of the losses in the specified system. Various techniques have been proposed to reduce these losses in the distribution entity. Among the common and most discussed technique for loss reduction in distribution system is the reactive power compensation by capacitor placement. Capacitor placement is implemented in two ways; shunt compensation (capacitors are placed in parallel with load) and series compensation (capacitors are placed in series with line). Series and shunt compensation helps to control and compensate thereactive power in the system, reducing the voltage regulation to make the voltage profile at the rated value, improving the power factor and enhancing the capacity of the power supplied to the load or customers. Byhaving all those as a result of capacitor placement implementation, the endconsumer as well as the powerutility companies will take the benefits in term of the reduced cost in supplying and consuming electrical power.